WebEx and Parature Team to Deliver Affordable Service Desk Solution for Companies of All Sizes; On-Demand Application Delivers Enterprise Customer Support Capabilities without the High Cost of On-Premise Software (PR Newswire, 2007)
The WebEx Support Center suite and its component applications provide a complete on-demand solution for customer support, customer service, IT help desk and desktop management. WebEx Remote Support allows end-users and employees to get connected instantly via the web to subject matter experts in customer support, a service contact center or an IT helpdesk and receive fast resolution to their issues. WebEx Remote Access customers can manage an entire IT or field device infrastructure from a centralized management console while protecting and securing assets. WebEx System Management enables customers to remotely support and manage employees' desktops and customers' systems. Parature is the global leader in on-demand customer support and help desk software. Our web-based support suite enables organizations to fundamentally change the way they support their customers while significantly reducing costs. The Parature suite of modules empowers associations, businesses, educational institutions, and government agencies with the ability to provide critical service information on a 24/7 basis while reducing the inbound support load through customer self-service. As a Software-as-a-Service (SaaS) provider, Parature delivers solutions over the Internet using a secure, scalable application and system architecture, which allows our customers to eliminate expensive up-front hardware and software costs and to quickly deploy and adopt our on-demand software. Parature helps support over 6,000,000 end- users worldwide and is headquartered in Vienna, VA. For more information about Parature please visit http://www.parature.com or call 1.877.GO.PARATURE. With 2.3 million registered users, WebEx is the global leader in on-demand applications for collaborative business on the web. These applications enhance high-touch business processes, such as sales and training, with efficient web-touch interactions. As an on-demand provider, WebEx is able to facilitate both internal and external collaboration. WebEx delivers its range of applications over the WebEx MediaTone Network, a global network specifically designed for the secure delivery of on-demand applications. WebEx applications support multipoint video conferencing, web conferencing, telework and application remote control. Please call toll free 877-509-3239 or visit http://www.webex.com for more information